2015
DOI: 10.1515/amm-2015-0257
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Repair Welded Joint On The Life Of Steam Pipeline Made Of Cr-Mo Steel Serviced Beyond The Calculated Working Time

Abstract: The aim of the paper was to examine the influence of repair welded joints on the service life of steam pipelines for over 220 000 hours of service in creep conditions. The research included the study of the microstructure using scanning microscopy, the tests on mechanical properties at room and elevated temperature, determining the nil ductility transition temperature, and short-time creep tests to determine the residual life of the material. The tests allowed determining the time of further safe operation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Recorded images of microstructure were used in the analysis of mean diameter of precipitates observed mainly on boundaries of martensite laths and grains of former austenite, where, according to the conducted internal research, confirmed with reference data [1,12], mainly M 23 C 6 carbides and Laves' phase are present.…”
Section: Microstructurementioning
confidence: 78%
See 1 more Smart Citation
“…Recorded images of microstructure were used in the analysis of mean diameter of precipitates observed mainly on boundaries of martensite laths and grains of former austenite, where, according to the conducted internal research, confirmed with reference data [1,12], mainly M 23 C 6 carbides and Laves' phase are present.…”
Section: Microstructurementioning
confidence: 78%
“…A crucial tool in diagnostic testing of material condition, not only within the design work time, but also beyond the design work time is a database of material characteristics. It takes into consideration changes in the processes of microstructure and mechanical properties degradation [9][10][11][12]. A significant factor having impact on the changes in microstructure, and thus functional properties, is the temperature, and in particular, its changes during exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] describing the structure of the data set change in time, and the analysed distributions show right-side asymmetry and concentration around the mean that are stronger than those in the normal distribution. Then, the probability density distributions were determined by non-parametric methods.…”
Section: Description Of the Structure Of The Data Setmentioning
confidence: 99%
“…Out of them, the components working at above the limit temperature, that is, under creep conditions, are of particular importance. In the assessment of these components, it is important and necessary to assess the condition of their materials [1][2][3][4][5][6][7]. Such an assessment is carried out based on nondestructive materials testing, and its result is referred to the available characteristics of materials after service [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%